Novel method for determining sex of live adult Laricobius nigrinus (Coleoptera: Derodontidae). Issue 6 (31st March 2014) - Shepherd, William P.; Montgomery, Michael E.; Sullivan, Brian T.; Mayfield, Albert E.
Abstract A method for determining the sex of live adult Laricobius nigrinus Fender (Coleoptera: Derodontidae) is described. Beetles were briefly chilled and positioned ventral-side-up under a dissecting microscope. Two forceps with blunted ends were used to gently brace the beetle and press on the centre of the abdomen to extrude its terminal segments. Male beetles were distinguished by a sclerotised, reticulate ninth abdominal sternite. In females, the distinct ovipositor (tergite, valvifers (ninth sternite), and laterotergites of the ninth abdominal segment) was visible. The procedure was rapid and harmed only a small number of individuals (fewer than 5%).